Vocabulary Acquisition: Practical Strategies for ESL Students - Min, Young-Kyung (Journal of International Students, 2013)
The English language is considered to have the largest vocabulary in the world (Crystal, 2002). Educated native speakers of English are expected to know approximately 20,000 word families or 70,000 words (Nation, 2001); however, educated non-native speakers of English know less than one quarter of the native speakers’ vocabulary (Laufer & Yano, 2001). Nonnative speakers of English must increase their vocabulary knowledge in order to become successful in their academic endeavors in English-medium educational environments. A solid foundation of vocabulary knowledge is essential at every stage of the learner’s second language (L2) development. Regardless of the degree of the learner’s competency in grammar and pronunciation; one cannot have effective communication without sufficient vocabulary knowledge.